Acute Generalized Exanthematous Pustulosis Induced by Etanercept: Another Dermatologic Adverse Effect. (20th March 2013) - Kavala, Mukaddes; Zindancı, Ilkin; Türkoglu, Zafer; Can, Burçe; Kocatürk, Emek; Senol, Serkan; Topaloglu, Filiz
Abstract : Acute generalized exanthematous pustulosis (AGEP) is a skin eruption that is primarily drug induced and characterized by the formation of numerous acute and sterile pustules on an erythematous background as mentioned by Weinblatt et al. (1999). We present a case of AGEP, following administration of etanercept, an antitumour necrosis factor alpha (TNF- α ) antibody, in a patient with psoriasis. Recognition of this reaction pattern is important given the frequent reliance on etanercept in treating psoriasis.